Influence of 7R in Logistics Industry towards Customer Satisfaction - Suresh, S.; S.Vasantha, Dr. (International Journal of Engineering and Technology, 2018)
7Rs of Logistics adequate material while producing/ modelling/accumulating a material, the industry would observe to the productivity challenges that can impact during movements. Quality packing needs, for example, shall arise from the material’s tons or containing bulk, its design or its easily broken and transporting distance. Material when shaped with required qualities shall amazedly easily facilitate transporting if they make some terms of standardization in the material’s sizes during the producing will make package, stocking, material handling and movements considerably facilitate.The Right customer is creating awareness for our material and quality of services. Facing biggest problem is identifying the customer to be targeted. The results to searching the right customer shall be to do a research in logistics markets. The research shall find an insight to which we are supposed to finalize. Then as per the cost one would select which survey procedures to deploy so that the right people know about our material and how to handle the material.Right Quantity is a key factor in logistics industry. If we don’t reach the demand of material, we shall losing money. Also if we have additional quantity our storage cost and other related expenses shall revise. So the manufacturing material should be based on the demand and do not make huge stocking expenses.The right condition in logistics is for the damage free delivery of the customer ordered product. The quality of the materials must be maintained till the time it reaches the destination. The supplying procedures must be such thatit is maintain the quality of the material without any additional cost.The demand for your material may vary place to another place. It si necessary to understand from doing additional market survey the proper place that needs to be targeted, as certain places should have demand for the material whereas the other places should not take care about the materials.On time delivery of materials is most important one, All process done but the entire process may fail if the timing is not right. For example it is essential to have the materials on the warehouse at the right time to supply to the customer, in case the product demand is not met at the right time it might be lost to customer. On time is all in this form of sales. It is necessary to make a schedule and stick to it in order to facilitate a smooth and efficient functioning.The study covers above all 7 rights in the logistics industry.